DESIGN AND DEVELOPMENT of FINANCIAL FLOW MOSQUE INFORMATION SYSTEM (SIKEMAS) USING CLIENT SERVER-BASED OBJECT ORIENTED - Diana Effendi; Rani Puspita Dhaniawaty; Mia Fitriawati; Muhammad Yasir Mumtaz2 (STMIK Royal, 2023)
Abstract: DKM has objectives such as overseeing the security and orderliness of the mosque as a whole, and managing the financial flows that exist within the mosque. Financial flow is a means of cash flow in a period related to the responsibility of company or agency management in managing cash both from operational, funding and investment activities. In managing current financial flows, DKM Masjid Al Ashlah Kopo Bandung still uses conventional manual recording methods. Such a system raises problems, including documentation of donors, calculations of zakat to be paid by congregations that are not in accordance with procedures. This makes the management and recording of cash flows less effective and efficient and also makes the management of the Bendahara DKM limited. SiKeMas is a system that has the goal of providing convenience in facilitating various DKM needs in managing financial flows, as well as informing DKM about the management of financial flow data. The research method used is the Object Oriented approach with various tools the design uses the UML. The system development is carried out using the prototype method. The results of this research are an application based on Desktop Client-Server with JAVA NetBeans IDE 7 and MySQL DBMS. Keywords: DKM; Financial Flow; SiKeMas; Abstrak: DKM memiliki tujuan antara lain mengawasi keamanan dan ketertiban masjid secara keseluruhan, serta mengelola aliran keuangan yang ada di dalam masjid. Arus keuangan merupakan sarana arus kas dalam suatu periode yang berkaitan dengan tanggung jawab manajemen perusahaan atau instansi dalam mengelola kas baik yang berasal dari kegiatan operasional, pendanaan maupun investasi. Dalam mengelola aliran keuangan saat ini, DKM Masjid Al Ashlah Kopo Bandung masih menggunakan metode pencatatan manual yang konvensional. Sistem seperti itu menimbulkan masalah, antara lain dokumentasi donatur, perhitungan zakat yang harus dibayarkan jamaah tidak sesuai prosedur. Hal ini membuat pengelolaan dan pencatatan arus kas menjadi kurang efektif dan efisien serta membuat pengelolaan DKM Bendahara menjadi terbatas. SiKeMas merupakan sistem yang bertujuan untuk memberikan kemudahan dalam memfasilitasi berbagai kebutuhan DKM dalam mengelola aliran keuangan, serta menginformasikan kepada DKM tentang pengelolaan data aliran keuangan. Metode penelitian yang digunakan adalah pendekatan Object Oriented dengan berbagai tools perancangan menggunakan UML. Pengembangan sistem dilakukan dengan menggunakan metode prototype. Hasil dari penelitian ini adalah sebuah aplikasi berbasis Desktop Client-Server dengan JAVA NetBeans IDE 7 dan MySQL DBMS. Kata kunci: Arus Keuangan; DKM; SiKeMas;